Volumetric deformations at early age on portland cement pastes with the addition of illitic calcined clay - Rossetti, Agustín (2020)
With the aim of reducing the environmental impact associated with cement production, during the last decade, different percentages of clinkers have been replaced in cement by supplementary cementitious materials (SCMs). When new SCMs are incorporated in concrete, it is necessary to evaluate, not only the mechanical properties (as strength and stiffness) and the durability but also the deformations that can generate cracking and decrease the service life of the structures. This paper is focused on the study of volumetric changes at the early ages of pastes made with blended cements with the addition of illitic calcined clays from the Buenos Aires province, Argentina. The objective of this work is to present preliminary studies on the effect of illitic calcined clays on the autogenous and chemical shrinkage of pastes. The studies were made on pastes (water/cementitious material ratio equal to 0.275) using a Portland cement type II/A-L, with the incorporation of different percentages (10%, 20% and 30%) of illitic calcined clays. A device for direct deformation measurement was used to register linear dimensional changes; the general guidelines of ASTM C 1608 were applied for the determination of chemical and autogenous shrinkage. The volumetric changes measured with direct device are the sum of the chemical and autogenous shrinkage accompanied with the expansion due to the heat released during hydration. It was found that pastes incorporating calcined clays had early deformations similar to or lower than reference paste without clay.